In situ PCR: protocols and applications. - Nuovo, G J

(untitled) (Genome Research, 1995)
Many groups have now published data based on the in situ detection of PCR-amplified DNA and cDNA. As with standard in situ hybridization or PCR, variables that can affect in situ PCR results include type of fixative and time of fixation, protease digestion, and the composition of the amplifying solution and oligoprobe cocktail. Investigators new to the field of in situ PCR should first try direct incorporation of the reporter molecule into paraffin-embedded tissue sections. Although nonspecific DNA synthesis is generated under these conditions, one can develop the confidence of synthesizing DNA inside the nucleus and appreciate the importance of protease digestion time to successful RT in situ PCR. It is an arguable statement that the in situ detection of PCR-amplified DNA and cDNA will have a very strong impact on many diverse fields, such as oncogenesis, embryology, RNA trafficking, and detection of viral diseases, as it already has on our understanding of the pathogenesis of HIV-1 infection.